2023
DOI: 10.1063/5.0157696
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carrier recombination coefficients of 3C- and 6H-SiC: Insights into recombination mechanisms in stacking faults of 4H-SiC

Kazuhiro Tanaka,
Masashi Kato

Abstract: In recent years, 4H-SiC power devices have been widely employed in power electronic systems owing to their superior performance to Si power devices. However, stacking faults in 4H-SiC can degrade the device performance. Stacking faults can be considered as polytype inclusions in 4H-SiC. Carrier recombination in stacking faults is considered a cause for performance degradation. Understanding carrier recombination in different polytypes other than 4H-SiC can be helpful in understanding the mechanism of performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…© 2024 The Japan Society of Applied Physics lifetime in the bulk substrates. 49) Considering the reported radiative and Auger recombination coefficients (2 × 10 −12 cm 3 s −1 and 3 × 10 −31 cm 6 s −1 ), 47) we calculated contributions of the band-to-band and Auger recombination with the hole concentration of the sample with N Al of 3 × 18 cm −3 as shown in Figs. 2(a) and 2(b).…”
Section: Discussionmentioning
confidence: 99%
“…© 2024 The Japan Society of Applied Physics lifetime in the bulk substrates. 49) Considering the reported radiative and Auger recombination coefficients (2 × 10 −12 cm 3 s −1 and 3 × 10 −31 cm 6 s −1 ), 47) we calculated contributions of the band-to-band and Auger recombination with the hole concentration of the sample with N Al of 3 × 18 cm −3 as shown in Figs. 2(a) and 2(b).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can also be concluded that defects directly dominate carrier recombination, which affects the material performance. Several measurements have been performed to observe the carrier recombination process [22,23]. Among these techniques, microwave photoconductivity decay (µ-PCD) and time-resolved photoluminescence (TR-PL) are the highly sensitive measurements used to observe the minority carrier recombination process when the charge carrier density is low [24].…”
Section: Introductionmentioning
confidence: 99%